The Role of International Migration in Maintaining the Population Size of Hungary between 2000-2050 - LaśzloH́ablicsek; Paĺ Pet́er Tot́h (Hungarian Demographic Research Institute, 2002)
In this paper, we consider the potential of international migration to contribute positively to the population replacement in Hungary. This involves a break with the idea of closed population used until now in population projections. By elaborating population scenarios with possible migration patterns, we seek answers to the following questions:a) Provided that the present immigration and emigration remain constant, how many years are needed to slow down or to stop the decline and the ageing of population?b) In case we intend to have the same population size in 2050 as today and we intend to reach this goal by a one-time significant settling of migrants, then what number and composition (sex and age) of foreign citizens should be settled in 2000?c) According to the baseline variant of Hungarian population projections, what are the migration volumes that could offset the accelerating decrease and ageing of the population?d) What fertility, mortality and migration conditions could lead to a more sustainable development of the population?[...] In this paper the main tool for studying the demographic impact of international migration is the scenario-method. However, as a first experiment, this role is analysed only with regard to the population size and age structure. This means, among others, that we do not take into consideration the ratio of Hungarian and non-Hungarian emigration, or the composition of immigrants in terms of country of origin. We do not address the consequences for the communities left by the immigrants nor the possible consequences of increasing number of immigrants and thus their relative proportion in the population of Hungary - except for the simple demographic consequences. The main goal of the study is the identification of the general levels of the phenomena (first of all migration) necessary for having a more or less constant population size in Hungary in the next decades.
Keywords: 300; Internationale Migration; Bevölkerungsentwicklung; Bevölkerungsprognose; Ungarn